2021
DOI: 10.1055/s-0041-1725201
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Temporal Volume between Males and Females and the Influence of Age and BMI: A Cross-Sectional CT-Imaging Study

Abstract: Background The temple has been identified as one of the most compelling facial regions in which to seek aesthetic improvement—both locally and in the entire face—when injecting soft tissue fillers. Objective The objective of this study is to identify influences of age, gender, and body mass index (BMI) on temporal parameters to better understand clinical observations and to identify optimal treatment strategies for treating temporal hollowing. Methods The sample consisted of 28 male and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…[13][14][15] Previous studies have established a relationship between facial skeletonization, temporal hollowing, and postmenopausal sarcopenia. 16 In addition, data have shown that selective estrogen receptor modulators (SERMs) play a role in diminishing skin aging in this patient population. 17 In clinical practice, however, women of all age groups seek correction of temporal hollowing.…”
mentioning
confidence: 99%
“…[13][14][15] Previous studies have established a relationship between facial skeletonization, temporal hollowing, and postmenopausal sarcopenia. 16 In addition, data have shown that selective estrogen receptor modulators (SERMs) play a role in diminishing skin aging in this patient population. 17 In clinical practice, however, women of all age groups seek correction of temporal hollowing.…”
mentioning
confidence: 99%
“…In the same study, 9 the authors identified increasing BMI to be associated with greater temporal soft tissue volume, but not greater temporal skin surface, in males. In females, the effect was inverted: increasing BMI was associated with greater temporal skin surface, but not greater temporal soft tissue volume.…”
Section: Tissue Layersmentioning
confidence: 83%
“…Recent work has used three-dimensional (3D) CT imaging to quantify properties of the temporal fossa and identify differences in aging patterns based on gender, age, and body mass index (BMI). 9 As the temporal bone curved medially, the depth of the temporal fossa was determined by the temporalis muscle and temporal extension of the buccal fat pad. Independently from gender, age, and BMI, the deepest aspect of the temporal fossa was found to be located anteriorly and inferiorly.…”
Section: Tissue Layersmentioning
confidence: 99%
See 2 more Smart Citations